Ritus Al-Qur’an tentang Kematian - Abdul Ghoni; Dadan Rusmana (Jurnal Dirosah Islamiyah, 2023)
Among the popular religious practices in Islamic society that are of concern to scholars are about life cycle ceremonies and pilgrimages to the graves of figures believed to be the guardians of Allah to obtain blessings. Many popular religious practices in Islamic society that have been carried out in popular religious practices are quite diverse, including local Islam as opposed to universal Islam, practical Islam as opposed to textual Islam, popular Islam versus ulama Islam, symbolic Islam versus normative Islam, popular Islam opposed to official Islam, small tradition versus big tradition, real Islam versus normative Islam. Therefore, this will examine one of the diversity of death traditions in Indonesia, especially those carried out by Nahdiyin residents. Various events and traditions are sometimes associated with the reading of Surah Yasin in it so that this surah has become a staple meal at religious events. The researcher focuses on the relationship that exists between the religious rituals held and the reading of Surah Yasin in it. The values ​​of the Koran that live in this tradition include, first, that people place the Koran as a holy book, so that reading the chosen letter of the Koran in an activity is a form of reviving the Koran in everyday life. Second, the reading of selected surahs of the Qur'an serves as a guard from various kinds of disturbances. Third, reading the chosen letter of the Koran is able to reduce the fears that will occur in the fetus it contains. The conclusion of this study is that the tradition of memitu is understood as gratitude which perceives the values ​​of the Qur'an as a source of holiness, protection and peace. Keywords: Al-Qur'an, Rites of death, Islam